2022
DOI: 10.1039/d2ce00229a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced luminescence of single-benzene fluorescent molecules through halogen bond cocrystals

Abstract: Organic single fluorescent molecules often suffer from aggregation-induced quenching effect under solid-state conditions, especially for red-emissive molecules, due to the flat rigid molecular framework and strong π-π interaction. Cocrystal engineering...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…The single components with a single aromatic ring showed no or weak fluorescence both pre and postradiation (Figures S52–S57). This is expected as these single-component phases are known for being relatively weak fluorophores due to aggregating-induced quenching within the solid state . Turning to the multicomponent phases, we note differing levels of quenching of the fluorescence signal for the preradiation samples.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The single components with a single aromatic ring showed no or weak fluorescence both pre and postradiation (Figures S52–S57). This is expected as these single-component phases are known for being relatively weak fluorophores due to aggregating-induced quenching within the solid state . Turning to the multicomponent phases, we note differing levels of quenching of the fluorescence signal for the preradiation samples.…”
Section: Resultsmentioning
confidence: 64%
“…This is expected as these single-component phases are known for being relatively weak fluorophores due to aggregating-induced quenching within the solid state. 56 Turning to the multicomponent phases, we note differing levels of quenching of the fluorescence signal for the preradiation samples. This has been previously noted to occur by Tamuly et al where they indicated 1,3-C 6 H 6 CO 2 and 1,4-C 6 H 6 CO 2 will engage in hydrogen bonding interactions with nitrogen-containing fluorophores to induce quenching in solution.…”
Section: ■ Introductionmentioning
confidence: 88%
“…However, the π–π stacking structure might cause fluorescence quenching and decrease quantum yield. 60–62…”
Section: Resultsmentioning
confidence: 99%
“…Noncovalent interactions, such as hydrogen bonding (HB), halogen bonding (XB), electrostatic, dipole-dipole and van der Waals interactions, represent an essential set of tools for the building of supramolecular architectures with precisely controlled structures and functions. [1][2][3][4][5][6] Thanks to the dynamic and reversible properties of noncovalent interactions, supramolecular assemblies have been used in widespread applications such as catalysis, [7][8][9][10] solar cells, [11][12][13] crystal engineering, 14,15 sensors, 16,17 and stimuli-responsive and selfhealing materials. [18][19][20][21][22][23] Among these interactions, XB has become increasingly attractive as a routine and predictable tool in supramolecular chemistry, due to its highly directional nature, significant strength, and tunable length.…”
Section: Introductionmentioning
confidence: 99%